"Elaboración de una guía interpretativa para el museo Municipal del catón Quevedo, año 2020" - Mayorga Andriance, Gissela Nathaly (2020)
The following research project was aimed at developing an interpretive guide for the Municipal Museum of Quevedo canton, Los Ríos province, through which the population will benefit from cultural and educational aspects, promoting teaching and learning about heritage, collecting information that contributes to generate interest in the local population for its culture and the visit of tourists in order to boost the economy of the city. Field visits were carried out thus determining the diagnosis of the current situation of the place, through which the state of conservation in which the archaeological objects are found and their organization in the Museum is observed, through this study it was carried out a survey to determine the level of knowledge that the population has about the Museum and how it contributes to society. Finally, the guide is structured according to the answers obtained in the surveys, providing interest in a creative, attractive and useful way for those who wish to know more about Quevedo archaeological cultural heritage. Keywords: Interpretive guide, archaeological objects, museum